Integrative bioinformatics analysis and experimental validation reveals key genes and regulatory mechanisms in the development of gout - Yuan, Ye; Gao, Zhiqiang; Chen, Jianhong; Liu, Yuejing; Zhou, Jingguo (Frontiers in Genetics, 2025)
Background and AimsGout is a prevalent inflammatory arthropathy caused by monosodium urate crystal deposition, yet its molecular pathogenesis remains incompletely understood. This study aimed to identify key genes and elucidate regulatory mechanisms underlying gout development through bioinformatics analysis combined with experimental validation.MethodsTranscriptome dataset GSE160170 and single-cell dataset GSE211783 were analyzed using differential expression analysis and weighted gene co-expression network analysis (WGCNA). Functional enrichment, protein-protein interaction (PPI), ceRNA, and transcription factor networks were constructed. Immune cell infiltration was analyzed using CIBERSORTx. Molecular docking predicted therapeutic compounds. Experimental validation included qRT-PCR, Western blot, gene knockdown/overexpression, and functional assays.ResultsAmong 329 gout-related genes identified, CXCL8, PTGS2, and IL10 emerged as key regulators involved in cell-cell adhesion, leukocyte activation, and NF-κB signaling. Immune infiltration revealed significant upregulation of M2 macrophages, activated mast cells, activated NK cells, and γδ T cells in gout samples. CeRNA network identified KCNQ1OT1 and hsa-mir-98-5p as regulatory elements, while CEBPB, STAT3, RELA, and NFKB1 were key transcription factors. Molecular docking suggested pergolide as a therapeutic candidate. Single-cell analysis confirmed high expression of key genes in T/NK cells and myeloid cells. Western blot validation showed upregulated protein expression of key genes in the gout model. PTGS2 knockdown enhanced cell viability and reduced apoptosis, while overexpression promoted inflammatory cytokine production and NF-κB pathway activation.ConclusionThis study systematically elucidated the pivotal roles of CXCL8, PTGS2, and IL10 in gout pathogenesis, providing valuable molecular targets for therapeutic development.